TEACHING FORENSIC MEDICINE TO MEDICAL STUDENTS: MODERN APPROACHES AND CHALLENGES - Haydarova Nargizaxon Axtamjon kizi, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract Forensic medicine, also known as legal medicine, is a vital field that bridges the gap  between  medicine  and  law.  As  medical  education  advances,  the  necessity  to provide students with comprehensive and practical knowledge in forensic medicine has become  increasingly  important.  This  article  explores  modern  methodologies  for teaching forensic medicine, the challenges educators face, and strategies to enhance student engagement and comprehension in this discipline.